Suicide Risk Protocols: Addressing the Needs of High Risk Youths Identified through Suicide Prevention Efforts and in Clinical Settings. Issue 2 (23rd December 2012) - Heilbron, Nicole; Goldston, David; Walrath, Christine; Rodi, Michael; McKeon, Richard
<x xml:space="preserve">Abstract</x> Several agencies have emphasized the importance of establishing clear protocols or procedures to address the needs of youths who are identified as suicidal through suicide prevention programs or in emergency department settings. What constitutes optimal guidelines for developing and implementing such protocols, however, is unclear. At the request of the Substance Abuse and Mental Health Services Administration, we provide an overview of recommendations, as well as steps taken in conjunction with selected prevention programs and in emergency department settings to address the needs and improve the care of these youths.